VALUE-ADDED: CONSULTING MIKHAIL BAKHTIN ABOUT WESTERN CHRISTIAN EUCHARIST - Green, Barbara (INTERAÇÕES, 2015)
In this study, I aim to demonstrate how Bakhtin's basic dialogic framework-specifically his understanding of how an author constructs a hero from which can be extrapolated how any one of us constructs an other - can add insight to the ways in which we might understand the Eucharist so that its ritual character is more relevant, more aligned with nonviolence, and more available to draw on in "prosaic" life than we might think it to be. I sketch briefly three relevant discourses that offer access to the Eucharist: First, some basic points about the Eucharist as cultic, then an adumbration of the violence question, and finally the relevant contribution of Bakhtin. I will conclude with some implications and suggestions for the development of insights. KEYWORDS: Eucharist. Violence. Nonviolence. Bakhtin. Com esse estudo, assumo como objectivo demonstrar como o quadro dialógico fundamental de Bakhtin - especificamente o seu entendimento de como um autor constrói um herói, a partir do qual se pode determinar também a forma como se constrói o outro - pode abrir para uma forma de compreensão da Eucaristia em que o seu caráter ritual seja mais relevante, mais alinhado com a não-violência e de maior impacto na vida "prosaica". Esboço três breves discursos relevantes que conduzem à Eucaristia: em primeiro lugar, alguns pontos básicos sobre a Eucaristia como culto, em seguida, um esboço da questão da violência, e, finalmente, a principal contribuição de Bakhtin. Concluo com algumas implicações e sugestões para o desenvolvimento da proposta. PALAVRAS-CHAVE: Eucaristia. Violência. Não-violência. Bakhtin.